New Transfection Agents Based on Liposomes Containing Biosurfactant MEL-A - Nakanishi, Mamoru (MDPI, 2013)
Nano vectors are useful tools to deliver foreign DNAs, oligonucleotides, and small interfering double-stranded RNAs (siRNAs) into mammalian cells with gene transfection and gene regulation. In such experiments we have found the liposomes with a biosurfacant mannosylerythriol lipid (MEL-A) are useful because of their high transfer efficiency, and their unique mechanism to transfer genes to target cells with the lowest toxicity. In the present review we will describe our current work, which may contribute to the great advance of gene transfer to target cells and gene regulations. For more than two decades, the liposome technologies have changed dramatically and various methods have been proposed in the fields of biochemistry, cell biology, biotechnology, and so on. In addition, they were towards to pharmaceutics and clinical applications. The liposome technologies were expected to use gene therapy, however, they have not reached a requested goal as of yet. In the present paper we would like to present an approach using a biosurfactant, MEL-A, which is a surface-active compound produced by microorganisms growing on water-insoluble substrates and increases efficiency in gene transfection. The present work shows new transfection agents based on liposomes containing biosurfactant MEL-A.